2009
DOI: 10.1097/qad.0b013e328330ed8a
|View full text |Cite
|
Sign up to set email alerts
|

HIV serosorting as a harm reduction strategy: evidence from Seattle, Washington

Abstract: Objective We sought to estimate how serosorting may affect HIV prevalence and individual risk among MSM in Seattle, Washington, and how the results vary under different assumptions of HIV testing frequency, heterogeneity in sexual behavior, and condom use. Methods We developed a deterministic mathematical model of HIV transmission dynamics. Data from the 2003 random digit dial study of MSM conducted in Seattle, Washington (n = 400) are used to parameterize the model. Results Predicted population-level HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 25 publications
1
63
0
Order By: Relevance
“…The profound effects of sexual contact rate reductions were confirmed [47,51,58,63,64,79,88,96,97,115,116], and even stronger impacts were reported if the reductions occurred in both infected and at-risk individuals, or earlier in the epidemic [37,39,42]. In terms of unsafe sex, both direct [24,27,32,36,70,116] and indirect effects (increasing prevalence other sexually transmitted infections [33,67,68,111]) on causing more HIV infections have been suggested.…”
Section: Effects Of Parameter Uncertainty On Hiv Epidemic Forecastsmentioning
confidence: 91%
See 2 more Smart Citations
“…The profound effects of sexual contact rate reductions were confirmed [47,51,58,63,64,79,88,96,97,115,116], and even stronger impacts were reported if the reductions occurred in both infected and at-risk individuals, or earlier in the epidemic [37,39,42]. In terms of unsafe sex, both direct [24,27,32,36,70,116] and indirect effects (increasing prevalence other sexually transmitted infections [33,67,68,111]) on causing more HIV infections have been suggested.…”
Section: Effects Of Parameter Uncertainty On Hiv Epidemic Forecastsmentioning
confidence: 91%
“…The positive impact of HIV testing on preventing infection have been clearly illustrated in many studies [24,33,41,48,72,79,112], the total number of infections averted due to HIV testing has been estimated to be dramatically larger than the total number of those have been infected since the epidemic has settled amongst Australian MSM [72]. The epidemiological benefit would be greater if infected individual is tested earlier after infection [36,113].…”
Section: Effects Of Parameter Uncertainty On Hiv Epidemic Forecastsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] While intended to reduce HIV risk, such strategies may fail in practice due to factors such as inaccurate assessment of individual and partner serostatus, infrequent testing, failure to maintain the agreement, and lack of protection against STIs. [18][19][20][21] Shortcomings in assessing partner HIV risk have also been reported among heterosexuals. Research among STI clinic attendees has indicated that patients often misjudge their partners' past and current risk behavior 22 and sexual exclusivity.…”
Section: Introductionmentioning
confidence: 99%
“…10 Although some researchers have cautioned against serosorting, 11,12 studies and models have indicated that it can be an effective method of reducing HIV transmission compared to having unprotected anal intercourse (UAI) with men of unknown or discordant statuses. 13,14 To make it a viable option for risk reduction, individuals must know their own HIV status, accurately disclose their status, and learn their partner's status before making a decision about which sexual activities to engage in (if any), which role to take (if engaging in anal sex), and whether to use condoms. studies indicate racial differences in its effectiveness in preventing HIV, with serosorting being less protective among black MSM than among white MSM.…”
Section: Introductionmentioning
confidence: 99%